Selection of drought resistant maize lines. - Castañón, Guillermo (2006)
Drought is an important abiotic factor where maize is grown under rainfall conditions. In order to identify drought resistant lines, 77 S5 maize lines from the breeding program at Cotaxtla, Veracruz and four CML maize lines from CIMMYTwere evaluated under irrigation  (So) and drought stress (S1). Five indexes were applied to select drought tolerant lines. Four indexes use the grain yield as criteria for selection, these are, the drought index (DI), the arithmetic mean (AM), the geometric mean (GM), and the stress tolerance index (STI). The last index, (G+GxS), takes into consideration all the traits evaluated in the trial. In general, all measured characteristics were affected by the drought treatment. The DI the other indexes. DI selects germplasm with the lowest yields, while, AM, GM, STI and G+Gxs indexes selected the same lines and all of these displayed a superior mean yield in comparison to those that were selected by the DI index. Among the best 10%, five lines and the checks CML 273 y CML 274, were selected by most of the indexes. According with the results, the best option to select drought resistance material will be with the use of the G+GxS index.